THEORY PLANNED BEHAVIOR DALAM MENGANALISIS NIAT PETANI MELAKUKAN PEMBIAYAAN ALSINTAN MELALUI BANK SYARIAH - Waluyo, Alif; Ahzar, Fahri Ali; Nurohman, Yulfan Arif; Qurniawati, Rina Sari (Among Makarti, 2023)
ABSTRACTFarmers have limited agricultural tools and machines (alsintan) to create an effective and efficient agricultural system. Procurement of agricultural equipment requires large capital so financing assistance is needed. Potential financing can be done from sharia banks which do not yet serve much in the agricultural sector. The aim of this research is to determine the factors that influence farmers' intentions to finance agricultural machinery through sharia banks. The respondents of this research were farmers spread across three districts including: Sragen and Sukoharjo. The method used is a mix method or a combination of quantitative and qualitative methods. Data was obtained through questionnaires and interviews with 100 respondents. The data was analyzed using the SPSS application. Data analysis techniques use research instrument tests, classical assumption tests, model accuracy tests, multiple regression analysis and hypothesis testing. The test results show that the attitude, subjective norm and behavioral control variables included in the theory of planned behavior are not proven to influence farmers' intentions to finance machinery at sharia banks. The variables knowledge and religiosity have been proven to influence farmers' intentions to finance machinery at sharia banks.ABSTRAKPetani memiliki keterbatasan alat dan mesin pertanian (alsintan) untuk menciptakan sistem pertanian yang efektif dan efisien. Pengadaan alat-alat pertanian memerlukan modal yang besar sehingga diperlukan bantuan pembiayaan. Potensi pembiayaan dapat dilakukan dari bank syariah yang belum banyak melayani di sektor pertanian. Tujuan penelitian ini adalah untuk mengetahui faktor-faktor yang mempengaruhi niat petani untuk membiayai mesin pertanian melalui bank syariah. Responden penelitian ini adalah para petani yang tersebar di tiga kabupaten antara lain: Sragen dan Sukoharjo. Metode yang digunakan adalah metode campuran atau gabungan metode kuantitatif dan kualitatif. Data diperoleh melalui kuesioner dan wawancara terhadap 100 responden. Data dianalisis menggunakan aplikasi SPSS. Teknik analisis data menggunakan uji instrumen penelitian, uji asumsi klasik, uji keakuratan model, analisis regresi berganda dan uji hipotesis. Hasil pengujian menunjukkan bahwa variabel sikap, norma subjektif dan kontrol perilaku yang termasuk dalam teori perilaku terencana tidak terbukti mempengaruhi niat petani untuk membiayai mesin di bank syariah. Variabel pengetahuan dan religiusitas terbukti mempengaruhi niat petani untuk membiayai mesin di bank syariah.